Refugee women's and providers' perceptions of person-centered maternity care: a qualitative study in two refugee camps in Chad - Alexis Ngarmbatedjimal; Mahamat Abdelaziz; Vincent de Paul Allambademel; Aminata Diarra; Valentin Djerambete; Thérèse Kodjimadje; Samy Luketa; Robert Madjigoto; Yodé Miangotar; Alladoum Ndingayande; Salomon Tamira; Theodora Varelis; et al. (BMC, 2024)
Abstract Background Globally, mistreatment of women during labor and delivery is a common human rights violation. Person-centered maternity care (PCMC), a critical component of quality of care, is respectful and responsive to an individual's needs and preferences. Factors related to poor PCMC are often exacerbated in humanitarian settings. Methods We conducted a qualitative study to understand Sudanese refugee women's experiences, including their perceptions of quality of care, during labor and delivery at the maternities in two refugee camps in eastern Chad, as well as maternity health workers' perceptions of PCMC and how they could be better supported to provide this. In-depth interviews were conducted individually with 22 women who delivered in the camp maternities and five trained midwives working in the two maternities; and in six dyads with a total of 11 Sudanese refugee traditional birth attendants and one assistant midwife. In addition, facility assessments were conducted at each maternity to determine their capacity to provide PCMC. Results Overall, women reported positive experiences in the camp maternities during labor and delivery. Providers overwhelmingly defined respectful care as patient-centered and respect as being something fundamental to their role as health workers. While very few reported incidents of disrespect between providers and patients in the maternity, resource constraints, including overwork of the providers and overcrowding, resulted in some women feeling neglected. Conclusions Despite providers' commitment to offering person-centered care and women's generally positive experiences in this study, one of few that explored PCMC in a refugee camp, conflict and displacement exacerbates the conditions that contribute to mistreatment during labor and delivery. Good PCMC requires organizational emphasis and support, including adequate working conditions and ensuring suitable resources so health workers can effectively perform.